[Trinidad: a list of the lovely vegetation] - (:unkn) unknown (My University, 2009)
Coconut trees dominate this black and white photograph which captures the typical roadside vegetation in Trinidad.
Colour; Black and White; Style: Portrait; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Plants; Trees--Coconut; Rural roads